Psychometric Properties of the Assessment of Perceived Access to Care (APAC) Instrument. Issue 1 (January 2021) - Fortney, John C.; Pyne, Jeff M.; Hawrilenko, Matt; Bechtel, Jared M.; Moore, Dana; Nolan, John P.; Pfeiffer, Paul; Shushan, Stephanie; Shore, Jay H.; Bowen, Deb
Abstract : Valid measures of perceived access are needed to measure whether health care systems are providing adequate access. This research reports on the psychometric properties of the Assessment of Perceived Access to Care (APAC), which was administered to 1004 Community Health Center patients screening positive for psychiatric disorders. Known-group validity was good, with 6 of the 8 hypothesized associations between social determinants of access and perceived access being significant ( P < .01). Better access was significantly ( P < .01) correlated with more outpatient mental health visits, indicating good convergent validity. The test-retest Pearson correlation coefficient (0.64) was statistically significant ( P < .01). The APAC has acceptable psychometric properties.